Estrogen receptor alpha and beta in health and disease. Issue 4 (August 2015) - Jia, Min; Dahlman-Wright, Karin; Gustafsson, Jan-Åke
<x xml:space="preserve">Abstract</x> Estrogen receptors alpha (ERα) and beta (ERβ) are transcription factors that are involved in the regulation of many complex physiological processes in humans. Abnormal ER signaling leads to development of a variety of diseases, such as cancer, metabolic and cardiovascular disease, neurodegeneration, inflammation, and osteoporosis. This review provides an overview and update on ERα and ERβ in health and disease with focus on their role in cancer and metabolic disease and in the context of recent years' success in providing genome wide data on ER function. Furthermore, potential clinical applications and challenges are also discussed.